Second-trimester maternal serum alpha-fetoprotein elevation and its association with adverse maternal/fetal outcome: ten years experience - Anfuso, S.; Soncini, E.; Bonelli, et al., P. (Acta Biomedica Atenei Parmensis, 2007)
Background: Alpha-fetoprotein (AFP) is the major serum protein in the embryonic stage and in the early fetal stage. The aim of this study was to determine any possible association between an “unexplained” elevation of maternal serum alpha-fetoprotein (MSAFP) levels in the second trimester of pregnancy and adverse maternal/fetal outcome. Methods: A retrospective cohort study, was carried out in the University of Parma, by reviewing all triple tests that had been found positive for neural tube defect screening, showing an “unexplained” MSAFP elevation (32.5 multiples of the median [MoM]), which could not be ascribed to any apparent reason. These results were compared with those of negative controls (MSAFP <2.5 MoM) in order to evaluate the course and outcome of pregnancy. Statistical analysis was performed by chisquare test, Fisher’s exact test, Student’s t-test, and odds ratio calculation. Results:We reviewed 16,747 tests: 143 tests with high MSAFP levels were found, including 105 data already available. Out of them 21 tests were excluded from the study because of the presence of fetal malformations, chromosomal diseases, or late miscarriage. Among the 84 remaining pregnancies, 43 were significantly associated with increased rates of pregnancy pathology compared with the control group of 199 patients, with 25 complicated pregnancies. In addition, high MSAFP levels were correlated with a less favorable neonatal outcome in terms of low birth weight, Apgar score, and transfer to a neonatal intensive care unit. Conclusions: Unexplained elevation of MSAFP levels in the second trimester of pregnancy is associated with an adverse maternal/fetal outcome, possibly suggesting the need for a more strict management of pregnancies.